Nitrous oxide cryotherapy for primary periocular basal cell carcinoma: outcome at 5 years follow-up. Issue 12 (9th September 2010) - Moesen, I; Duncan, M; Cates, C; Taylor, A; Wintle, R V; Ismail, A; Lim, D Khan; Tyers, A G
Abstract : Aim: To report the outcome at 5-year follow-up of a defined series of patients with primary periocular basal cell carcinoma treated by cryotherapy using a nitrous oxide probe. Methods: A prospective, non-comparative, interventional case series. One hundred primary periocular basal cell carcinomas were treated with a double freeze–thaw cycle nitrous oxide contact cryotherapy probe. Inclusion criteria were clinically well-defined primary periocular basal cell carcinomas with maximum diameter of 8 mm. The main outcome measure was histologically proven recurrence rate at 5-year follow-up. Results: Kaplan–Meier survival analysis showed a 5-year recurrence rate of 8%. Cox regression analysis revealed no correlation between tumour site, tumour size, cryotherapy freeze time and recurrence (p=0.60, p=0.86 and p=0.71, respectively). Thirty-six per cent of patients were lost to follow-up at 5 years following treatment. Conclusion: The results of this series suggest that nitrous oxide probe cryotherapy for primary periocular basal cell carcinomas up to 8 mm diameter has a recurrence rate of ∼8%. Cryotherapy has certain advantages over surgical removal of tumours of this size in the periocular region, but careful follow-up is advisable.